Small bowel adenocarcinoma incarcerated within an inguinal hernia - Hironari Kawai; Koichiro Haruki; Naoki Takada; Toshio Iino; Masahiro Ikegami; Katsuhiko Yanaga (Surgical Case Reports)
Abstract Background Small bowel adenocarcinomas are rare malignant tumors that account for less than 2% of gastrointestinal malignancies. In addition, tumor incarceration in an inguinal hernia is also rare entity. We herein report a first case of small bowel adenocarcinoma incarcerated within an inguinal hernia. Case presentation A 75-year-old man with asymptomatic anemia (hemoglobin, 8.6 g/dl) had a checkup at our hospital. Colonoscopy revealed bleeding through the ileocecal valve and an annular stricture by a tumor in the ileum. Endoscopic biopsy revealed a well-differentiated adenocarcinoma of the small bowel. Enhanced computed tomography showed a hypervascular solid tumor incarcerated within a right inguinal hernia. With a diagnosis of small bowel adenocarcinoma incarcerated within a right inguinal hernia, the patient underwent elective laparotomy with midline excision. The small bowel tumor, located at 30 cm from the terminal ileum, was incarcerated within a right inguinal hernia, and the small bowel was adherent to the hernia sac. A 24-cm segment of the distal ileum and regional lymph nodes were resected. The hernia sac was ligated, and the bottom of the hernia sac was resected. The hernia orifice was closed by tissue repair technique via a standard oblique incision in the right inguinal region. Postoperatively, the patient remains well with no evidence of tumor or hernia recurrence as of 1 year after operation. Conclusions We reported to our knowledge the first case of small bowel adenocarcinoma incarcerated within an inguinal hernia.